2015
DOI: 10.1016/j.bpc.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of conformational changes in helix 69 mutants by pseudouridine modifications

Abstract: Centrally located at the ribosomal subunit interface and mRNA tunnel, helix 69 (H69) from 23S rRNA participates in key steps of translation. Ribosome activity is influenced by three pseudouridine modifications, which modulate the structure and conformational behavior of H69. To understand how H69 is affected by the presence of pseudouridine in combination with sequence changes, the biophysical properties of wild-type H69 and representative mutants (A1912G, U1917C, and A1919G) were examined. Results from NMR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The consecutive Ψ38 and Ψ39 residues in tRNA His provide stacking stabilization for bases on the 3′ side of the tRNA anticodon loop 17 . Also, the conserved Ψ modifications in helix 69 (H69) from large subunit ribosomal RNA have been shown to modulate the structure and conformational behavior of the stem-loop region by stabilizing the loop-closing base pair and promoting base stacking in the 3′ half of the loop 18,19 and an additional A-Ψ base pair within the loop 20 . The UV melting data revealed that the Ψ residues in the stem region provided thermodynamic stabilization to the RNA, whereas individual Ψs located in the loop region contributed to a slight destabilization 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The consecutive Ψ38 and Ψ39 residues in tRNA His provide stacking stabilization for bases on the 3′ side of the tRNA anticodon loop 17 . Also, the conserved Ψ modifications in helix 69 (H69) from large subunit ribosomal RNA have been shown to modulate the structure and conformational behavior of the stem-loop region by stabilizing the loop-closing base pair and promoting base stacking in the 3′ half of the loop 18,19 and an additional A-Ψ base pair within the loop 20 . The UV melting data revealed that the Ψ residues in the stem region provided thermodynamic stabilization to the RNA, whereas individual Ψs located in the loop region contributed to a slight destabilization 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Since previous chemical probing studies were consistent with conformational changes in the H69 loop upon subunit association, 35 this result suggests crosstalk between the H69 stem and loop regions on the ribosome level, which was previously observed in H69 model systems. 41,43 Such conformational rearrangements appear to affect the binding scaffold for aminoglycosides within the stem region of H69, as shown by the differences in DMS reactivity at G1922 ( i.e ., protection by neomycin or paromomycin) between isolated subunits and complete ribosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Helix 69 participates in almost every step of translation and establishes direct contacts with multiple translation factors . This helix was also identified as an antibiotic binding site. , With synthetic 19-mer RNA constructs of H69, the contribution of each residue to global thermodynamic stability was determined, allowing for a deeper understanding of the effects of mutations or loss of modifications in H69. , …”
Section: Modifications In H31 H44 and H69mentioning
confidence: 99%
“…In human H69, Ψ residues 3731 and 3733 (1915 and 1917 in E. coli ) are less destabilizing than their bacterial counterparts, with the difference in thermodynamic contributions of the modifications being attributed to the loop sequence (A1918 in bacteria compared with G1918 in eukaryotes) . Later studies in our laboratory revealed stem–loop crosstalk in H69, indicating that differences in the stem sequences of bacterial and human H69s can be propagated to the loop regions …”
Section: Modifications In H31 H44 and H69mentioning
confidence: 99%
See 1 more Smart Citation